Getting Down to Earth : Are Satellites Reliable for Measuring Air Pollutants That Cause Mortality in Low- and Middle-Income Countries? - World Bank (Washington, DC: World Bank, 2022)
Outdoor air pollution accounts for an estimated 4.2 million deaths worldwide, the majority of which are caused by exposure to fine particulate matter (or PM2.5) air pollution. Most of these deaths occur in low- and middle-income countries (LMICs). Reducing PM2.5 air pollution is thus crucial for improving public-health outcomes in those countries. Measuring and reducing the health impacts of PM2.5 is especially challenging in many LMICs because ground-level air-quality monitoring networks are typically nonexistent. Where they are in place, they are often not properly operated and maintained and are thus unreliable. Limited local expertise in air-quality measurement presents additional challenges. These shortcomings can undermine a country’s ability to design and implement effective policies to improve outdoor air quality. Satellite technology has been used successfully for measuring air quality in high-income countries where operation of ground-level air-quality monitoring networks is well established. However, Getting Down to Earth: Are Satellites Reliable for Measuring Air Pollutants That Cause Mortality in Low- and Middle-Income Countries? investigates the performance of satellites in LMICs for predicting outdoor concentrations of PM2.5, based on case studies in nine cities in different regions representing a range of environmental conditions (including mountainous, dusty, and coastal). The report finds that the satellite-derived estimates of PM2.5 in LMICs are associated with very large uncertainty, ranging from 21 percent to 85 percent depending on the model used for translating satellite measurements of aerosol optical depth—the parameter measured by satellites—to surface-level outdoor PM2.5 concentrations. This report shows that satellites are unreliable for estimating ambient concentrations of PM2.5 in LMICs. Furthermore, satellite-derived measurements cannot replace properly operated and maintained ground-level monitoring networks for measuring the concentrations of PM2.5 that human beings are typically exposed to daily. Thus, it is important that LMICs strengthen support for the establishment of ground-level monitoring networks to measure air pollutants, notably PM2.5, that cause mortality in Sub-Saharan Africa and other regions with LMICs.